2012
DOI: 10.5433/1679-0359.2012v33supl2p3163
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Lactobacillus casei in chocolate flan and its survival to simulated gastrointestinal conditions

Abstract: The aim of this work was to verify the viability of Lactobacillus casei in chocolate flan as well as its survival under simulated human gastrointestinal conditions. After 1 and 15 days of manufacture, the dessert was evaluated for L. casei population and subsequently submitted to acidic solution for 30, 60, 90 and 120 min and to bile salts solution for 150 min. After each time, L. casei population was evaluated. The results were evaluated by variance analysis (ANOVA) and Tukey's test. The population of L. case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…The un-supplemented coconut extract provided sufficient substrate for L. reuteri growth, due to the natural sucrose present in the matrix used as a source for bacterial multiplication. In this research, no reduction in viability was observed during storage, despite the increase in acidity, corroborating with several studies that reported the maintenance of the minimum viable amount of probiotic culture during storage ( Aragon-Alegro et al, 2007 ; Corrêa, Castro & Saad, 2008 ; Silva et al, 2012 ). The concentration of titratable acidity in the products is dependent on the raw material acid and the production of organic acids by the probiotic microorganism ( Lobato-Calleros et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…The un-supplemented coconut extract provided sufficient substrate for L. reuteri growth, due to the natural sucrose present in the matrix used as a source for bacterial multiplication. In this research, no reduction in viability was observed during storage, despite the increase in acidity, corroborating with several studies that reported the maintenance of the minimum viable amount of probiotic culture during storage ( Aragon-Alegro et al, 2007 ; Corrêa, Castro & Saad, 2008 ; Silva et al, 2012 ). The concentration of titratable acidity in the products is dependent on the raw material acid and the production of organic acids by the probiotic microorganism ( Lobato-Calleros et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies in the area reported reported that many manufacturers, after fermentation, submit the raw material to thermal treatments to guarantee the safety of the product, focusing in extending the shelf-life of the dairy desserts and pH in the final product must be around 6.2 and 6.5 (Silva et al, 2012); thus, the pH of the samples studied is above the range reported in the literature nevertheless, for the parameter pH, the new Normative Instruction Nº 84 (Brasil, 2020) did not indicate attributions, even being an important quality factor of dairy products.…”
Section: Titrable Acidity and Phmentioning
confidence: 99%
“…Figueiredo et al (2015) have developed a powdered milk supplemented with L. acidophilus and, although during drying of milk most cells die, the authors were able to conclude that production of this novel probiotic food is feasible. Silva et al (2012) produced a chocolate pudding with added L. casei , characterizing this dessert as an excellent carrier of probiotic microorganisms. Antunes et al (2007a, b) have developed butter and buttermilk probiotics, respectively: both new products presented the desired requirements regarding safety and the number of probiotic bacteria.…”
Section: Brazilian Scenario For Probiotics In the Dairy Industry: Devmentioning
confidence: 99%